Autophagy activation alleviates annulus fibrosus degeneration via the miR-2355-5p/mTOR pathway - Zilin Yu; Chunyang Fan; Yubo Mao; Xiexing Wu; Haiqing Mao (Journal of Orthopaedic Surgery and Research)
Abstract Background Intervertebral disc degeneration disease (IVDD) is a major cause of disability and reduced work productivity worldwide. Annulus fibrosus degeneration is a key contributor to IVDD, yet its mechanisms remain poorly understood. Autophagy, a vital process for cellular homeostasis, involves the lysosomal degradation of cytoplasmic proteins and organelles. This study aimed to investigate the role of autophagy in IVDD using a hydrogen peroxide (H2O2)-induced model of rat annulus fibrosus cells (AFCs). Methods AFCs were exposed to H2O2 to model oxidative stress-induced degeneration. Protein expression levels of collagen I, collagen II, MMP3, and MMP13 were quantified. GEO database analysis identified alterations in miR-2355-5p expression, and its regulatory role on the mTOR pathway and autophagy was assessed. Statistical tests were used to evaluate changes in protein expression and pathway activation. Results H2O2 exposure reduced collagen I and collagen II expression to approximately 50% of baseline levels, while MMP3 and MMP13 expression increased twofold. Activation of autophagy restored collagen I and II expression and decreased MMP3 and MMP13 levels. GEO analysis revealed significant alterations in miR-2355-5p expression, confirming its role in regulating the mTOR pathway and autophagy. Conclusions Autophagy, mediated by the miR-2355-5p/mTOR pathway, plays a protective role in AFCs degeneration. These findings suggest a potential therapeutic target for mitigating IVDD progression.